2018
DOI: 10.1161/circulationaha.117.031883
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Use of Shared Data From Cardiometabolic Clinical Trials

Abstract: , the platform had data from 3374 clinical trials, of which 537 (16%) evaluated cardiometabolic therapeutics (phase 1, 36%; phase 2, 17%; phase 2/3, 1%; phase 3, 42%; phase 4, 4%). They covered 74 therapies and 398 925 patients. Diabetes mellitus (60%) and hypertension (15%) were the most common study topics. Median time from study completion to data availability was 79 months. As of May 2017, ClinicalStudyDataRequest.com had received 318 submitted proposals, of which 163 had signed data-sharing agreements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Certain decisions contrast with other existing clinical trial data sharing initiatives (including those found at https://biolincc.nhlbi.nih.gov/studies/ , https://ClinicalStudyDataRequest.com/ , and https://dcri.org , as examples). For instance, the decision to reactively de-identify data for sharing in response to requests has meant that 68% of trials listed on the YODA Project website have been used, as opposed to platforms that have proactively de-identified data for sharing reporting that approximately 15% of listed trials having been used 32 , 33 . Similarly, while the direct, secure data transfer used for Medtronic rhBMP-2 trials was simple, the secure platform used for Johnson & Johnson’s trials is more challenging for investigators, particularly those without advanced statistical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Certain decisions contrast with other existing clinical trial data sharing initiatives (including those found at https://biolincc.nhlbi.nih.gov/studies/ , https://ClinicalStudyDataRequest.com/ , and https://dcri.org , as examples). For instance, the decision to reactively de-identify data for sharing in response to requests has meant that 68% of trials listed on the YODA Project website have been used, as opposed to platforms that have proactively de-identified data for sharing reporting that approximately 15% of listed trials having been used 32 , 33 . Similarly, while the direct, secure data transfer used for Medtronic rhBMP-2 trials was simple, the secure platform used for Johnson & Johnson’s trials is more challenging for investigators, particularly those without advanced statistical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…And indeed, there is almost no culture of performing and publishing re-analyses in the clinical trial literature (13), especially by entirely independent authors. Another survey of cardiometabolic clinical trials available on the clinical study data request platform (14) suggested that despite efforts to make data available, re-uses were rare. Over 4 years, only 3 re-uses had been published among the 537 studies available for access.…”
Section: Discussionmentioning
confidence: 99%
“…The progress in the yield from secondary research in terms of peer-reviewed publications has been cited as being relatively low. 20,3941 While this could be due to the natural lag in uptake of a relatively new phenomenon, it is in sharp contrast to the resounding cry for openness and availability of data. The jury is still out on the effectiveness of the approaches being taken.…”
Section: Difficulties With the Current Data Access Systemsmentioning
confidence: 99%